2014
DOI: 10.1111/1754-9485.12171
|View full text |Cite
|
Sign up to set email alerts
|

Comparison study of portable bladder scanner versus cone‐beam CT scan for measuring bladder volumes in post‐prostatectomy patients undergoing radiotherapy

Abstract: The BS produces bladder volume readings of an average 19.7% difference from CT-V or CBCT-V and can potentially be used to screen for large interfraction bladder volume variations in radiotherapy to prostatic bed. The observed interfraction bladder volume variation suggests the need to improve bladder volume consistency. Incorporating the BS into practice is feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…We found strong correlations (R = 0.91-0.96) between the BS and other devices (CT/CBCT/iU22), consistent with several previous studies. Some correlations reported were 0.96-0.99 between BVI9400 and actual voided urine/CT/CBCT, 17,18 0.91-0.97 between BVI6400 and CT, 5,19 and 0.88-0.95 between BVI3000 and CT. 20,21 The mean value of the time interval in our study was 2 min between CT/iU22 scans and BS measurements, 14 and 15 min between BS measurements and CBCT scans. Due to logistical issues, the time interval between BS measurements and the other equipment used in making these evaluations may be more than 10 min, which could account for the deviations observed.…”
Section: Discussionmentioning
confidence: 97%
“…We found strong correlations (R = 0.91-0.96) between the BS and other devices (CT/CBCT/iU22), consistent with several previous studies. Some correlations reported were 0.96-0.99 between BVI9400 and actual voided urine/CT/CBCT, 17,18 0.91-0.97 between BVI6400 and CT, 5,19 and 0.88-0.95 between BVI3000 and CT. 20,21 The mean value of the time interval in our study was 2 min between CT/iU22 scans and BS measurements, 14 and 15 min between BS measurements and CBCT scans. Due to logistical issues, the time interval between BS measurements and the other equipment used in making these evaluations may be more than 10 min, which could account for the deviations observed.…”
Section: Discussionmentioning
confidence: 97%
“…Wallice et al 10 suggested scanner accuracy as ‘appropriate for radiotherapy purpose’, namely verification of approximate bladder volume confirming adherence to drinking protocol. Ung et al 6 agreed accuracy is acceptable in detection of large inter-fraction variation. The focus groups agreed the bladder volume scanner was appropriate for purpose:…”
Section: Discussionmentioning
confidence: 93%
“…We found compliance with drinking protocol was not a guarantee of reproducible volume. Ung et al 6 suggested some causative factors for bladder volume variation during radiotherapy as individual patient hydration status, diurnal fluid balance variation, adequate pre-drinking void, varied renal re-absorption and impact of radiotherapy on inflow. Our study took a similar approach to O’Doherty et al, 15 and also followed the recommendations in Taylor and Powell 2 that drinking protocols be tailored to individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated glomerular ltration rate (eGFR) was estimated by the following conversion formula for Japanese men: eGFR (mL/min/1.73 m 2 ) = 194 × serum creatinine (SCr) −1.094 × age − 0.287 (10). For the post-void residual urine volume, the urine volume in the bladder immediately after urination was three-dimensionally measured with an ultrasonic diagnostic apparatus (Bladder Scan BVI 3000 or BVI 6100; Sysmex, Kobe, Japan) (11,12). Patient age was the age at the time of planning CT.…”
Section: Patient Characteristicsmentioning
confidence: 99%